Analisis Lingkungan Kerja, Motivasi Kerja dan Perilaku Kerja Karyawan Terhadap Semangat Kerja Karyawan Pada Era Pandemi Di Gramedia Bookstore Kediri - Rendra Tri Sanjaya; Edi Swasono; Mohammad Naim Musafik (Universitas Islam Kadiri, 2021)
Currently, the world has attacked a COVID-19 pandemic, including Indonesia. This has an impact on economic stability and limit people's activities to carry out daily activities, especially at work. This study aims to determine the effect of the work environment, work motivation and employee behavior on employee morale during the pandemic era at Gramedia Bookstore Kediri. The sampling technique in this study uses a saturated sampling technique, which is a sampling technique when all members of the population are used as samples. The sample in the study was 30 employees of Gramedia Bookstore Kediri. The analycal techniques that used are validity test, reliability test, descriptive analysis, classical assumption test, multiple linear regression analysis, hypothesis testing, t test and F test. The results of the research partially show that the variables of the work environment, work motivation and work behavior of employees have a significant and significant influence on the variable of employee morale. Meanwhile, simultaneously it was found that the variables of work environment, work motivation and work behavior of employees affect the variable of employee morale, and the most dominant variable affecting the variable of employee morale is the work environment variable. The results of this study imply that the work environment, work motivation and work behavior of employees are related and very important in increasing employee morale in these conditions.